A multi‐repeat adhesin of the phytopathogen, Pectobacterium atrosepticum, is secreted by a Type I pathway and is subject to complex regulation involving a non‐canonical diguanylate cyclase - Pérez‐Mendoza, Daniel; Coulthurst, Sarah J.; Humphris, Sonia; Campbell, Emma; Welch, Martin; Toth, Ian K.; Salmond, George P. C. (Molecular microbiology, 2011)
Summary Cyclic diguanylate (c‐di‐GMP) is a second messenger controlling many important bacterial processes. The phytopathogen Pectobacterium atrosepticum SCRI1043 (Pba1043) possesses a Type I secretion system (T1SS) essential for the secretion of a proteinaceous multi‐repeat adhesin (MRP) required for binding to the host plant. The genes encoding the MRP and the T1SS are tightly linked to genes encoding several putative c‐di‐GMP regulatory components. We show that c‐di‐GMP regulates secreted MRP levels in Pba1043 through the action of two genes encoding predicted diguanylate cyclase (DGC) and phosphodiesterase proteins (ECA3270 and ECA3271). Phenotypic analyses and quantification of c‐di‐GMP levels demonstrated that ECA3270 and ECA3271 regulate secreted MRP levels by increasing and decreasing, respectively, the intracellular levels of c‐di‐GMP. Moreover, ECA3270 represents the first active DGC reported to have an alternative active‐site motif from the ‘canonical’ GG[D/E]EF. ECA3270 has an A‐site motif of SGDEF and analysis of single amino acid replacements demonstrated that the first position of this motif can tolerate functional substitution. Serine in position one of the A‐site is also observed in many other DGCs. Finally, another T1SS‐linked regulator (ECA3265) also plays an important role in regulating secreted MRP, with an altered localization of MRP observed in an ECA3265 mutant background. Mutants defective in these three T1SS‐linked regulators exhibit a reduction in root binding and virulence, confirming that this complex, finely tuned regulation system is crucial in the interaction with host plants.